Plaque Ablation by Excimer Laser Irradiation Using a Movable Energy-Transmitting Device - Laufer, Günther (1987)
During the past 2 years, excimer laser energy has been shown to provide a highly suitable type of atherosclerotic plaque ablation, especially in small-diameter vessels such as coronary or crural arteries. Nevertheless, transmission of far-ultraviolet pulsed laser power has remained a major problem in animal studies and clinical trials. In an attempt to solve this problem, we constructed an energy-transmitting device for use with a Lambdaphysics EMG 102 excimer laser. The transmission system, which was housed in a rigid articulated arm, allowed movement in all directions and rotation along the long axis, thus permitting easy handling and guiding of the laser beam in the operating field. To test whether this device could deliver enough energy to remove atherosclerotic plaques within a period that would meet the requirements for intraoperative use, we obtained fresh human cadaver coronary arteries both with and without atherosclerotic disease, and irradiated them vertically and coaxially. A power meter was used to determine the effective amount of energy delivered at the distal end of each vessel. Energy densities up to 3 J/cm(2)/pulse were obtained, owing to energy focussing within the transmitting device. At 5 Hertz (Hz), tissue ablation consisted of approximately 20 μm/pulse. Areas of normal vascular tissue, as well as fibrohyalinous and lipid plaque components, were promptly ablated. Macroscopically, the “lasered holes” appeared well-circumscribed, with clear-cut surfaces and no carbonization. Light microscopy revealed no thermal damage to the boundary tissue. With this new energy-transmitting device, the surgeon can use excimer laser irradiation intraoperatively. There is no significant loss of energy between the generator and the tip, and energy densities of 3 J/cm(2)/pulse are available for sufficient plaque removal. (Texas Heart Institute Journal 1987; 14:47-52)